PENGARUH TERAPI RELAKSASI DZIKIR TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI PADA MASYARAKAT DI DAERAH TAMAN RAYA RAJEG - Oktaviani Pratiwi; Yuliana Yuliana (Nusantara Hasana Berdikari, 2022)
Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a state of sufficient rest or calm. The type of research used is quantitative research with a semi-test research design or a semi-trial design. The population in this study was 30 respondents. The sampling technique used was total sampling. The statistical test used is the Wilcoxon test. The results of the Wilcoxon signed ranks test in the intervention and control groups both before (pre-test) and after (post-test) obtained p-value (0.001) < (0.05) then H0 is rejected, meaning that there is an effect of dhikr relaxation therapy on hypertension patients, both pre-test and post-test. There is a significant effect in the intervention and control groups on hypertension on the effect of dhikr relaxation therapy on the level of stress reduction for hypertension sufferers in the community in the Taman Raya Rajeg area, namely P-Value 0.001 (P <0.005).